Needs Analysis of Aircraft Mechanics’ English Language Skills - Peter Korba; Ingrid Sekelová; Branko Mikula; Martina Koščáková (Aerospace, 2023)
English is used in all parts of aviation, especially in aircraft maintenance, where all documentation and various manuals are written in this language. However, there are no formal requirements for aircraft mechanics to have a certain level of English. Nevertheless, aircraft mechanics must master their English language skills, since they are needed for managing their work tasks. This study deals with the issue of insufficiency of standardized English courses, and determines the English language needs of aircraft maintenance in the Slovak Republic, using a triangular approach. The gathered data from 80 respondents for this paper were subjected to descriptive and inferential statistics, which were calculated by the means of Jamovi statistical software. The results revealed that aircraft mechanics engage most often in communication situations that require their knowledge of the reading skill. The importance of all language skills (reading, writing, listening, speaking) is proven by the determination of the most-common communication activities of aircraft mechanics, which should be included in specialized English courses. The results of this study are useful in the creation of language courses which increase the level of English in aircraft maintenance, thus, increasing safety in aviation.